A critical analysis of prophylaxis to avoid venous thromboembolism after cesarean delivery (Annals of Medical Research, 2021)
Aim: The aim of the present study was to analyze the risk factors for VTE in patients who underwent cesarean section. Pregnancy is a thrombogenic condition, and pregnant women have a five-to-six fold higher risk of VTE than non-pregnant women. The incidence of VTE is two-to-four times higher in cesarean deliveries than in vaginal deliveries.Material and Methods: 450 pregnant women who delivered by cesarean section were analyzed. The Turkey Ministry of Health Risk Pregnancy Management Guidelines was used to determine the VTE risk and its factors. After analyses of the data, the number and proportion of high-risk patients, that of medium-risk patients, and that of patients were determined.Results: After analyzing the risk factors we found that 59 (13.1%) pregnant women had a high risk, 351 (78%) had a moderate risk, and 40 (8.9%) had a low risk for VTE. In risk factor analyses, 9 women (2%) in the high-risk group had a history of VTE, 9 (2%) had a high risk of thrombophilia, 9(2%) had a low risk of thrombophilia and a family history of VTE, and 32(7.1%) needed low molecular–weight heparin during the antenatal period. When moderate-risk patients were classified for VTE, we found that 151 (33.6%) had two or more minor risk factors, 117 (26%) required cesarean section during labor, 42 (9.3%) had a hospital stay >3 days or were readmitted after delivery, 32 (7.1%) had a systemic disease, and 9 (2%) had a BMI>40 kg/m2. Conclusion: The results of the study suggest that the majority of pregnant women should be given VTE prophylaxis after cesarean delivery.